2014
DOI: 10.1371/journal.pone.0115245
|View full text |Cite
|
Sign up to set email alerts
|

Negative Association between Serum Parathyroid Hormone Levels and Urinary Perchlorate, Nitrate, and Thiocyanate Concentrations in U.S. Adults: The National Health and Nutrition Examination Survey 2005–2006

Abstract: ObjectivesPerchlorate, nitrate, and thiocyanate are well-known inhibitors of the sodium-iodide symporter and may disrupt thyroid function. This exploratory study investigated the association among urinary perchlorate, nitrate, and thiocyanate concentrations and parathyroid hormone (PTH) levels in the general U.S. population.MethodsWe analyzed data on 4265 adults (aged 20 years and older) from the National Health and Nutrition Examination Survey in 2005 through 2006 to evaluate the relationship among urinary pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Some of these data are comparable to what was observed in this study but UGMs for females are substantially higher for this study than what was reported by Ko et al [7]. Also, while USCN levels were higher for NHW in this study than NHB, the reverse relationship was reported by Ko et al [7]. Authors investigated the reasons for these discrepancies and found the explanation.…”
Section: Levels Of Uscnsupporting
confidence: 88%
See 3 more Smart Citations
“…Some of these data are comparable to what was observed in this study but UGMs for females are substantially higher for this study than what was reported by Ko et al [7]. Also, while USCN levels were higher for NHW in this study than NHB, the reverse relationship was reported by Ko et al [7]. Authors investigated the reasons for these discrepancies and found the explanation.…”
Section: Levels Of Uscnsupporting
confidence: 88%
“…Authors investigated the reasons for these discrepancies and found the explanation. Ko et al [7] computed the UGMs for USCN without making any adjustments for urine creatinine and we were able to almost match their UGMs for 2005-2006 data. However, as has been recommended by [17], we used urine creatinine in the models to adjust for urine creatinine.…”
Section: Levels Of Uscnmentioning
confidence: 68%
See 2 more Smart Citations
“…Therefore, monitoring of ion concentration changes in human blood is successfully performed as a basic analysis in medical diagnostics [57]. It is known that the ionic composition of saliva may reflect the health state of the person being examined [58][59][60][61][62]. Due to the correlation of ion concentration with the general health status, the potentiometric measurements can be applied to the assessment of ionic profiles in saliva [62].…”
Section: Introductionmentioning
confidence: 99%